Effect of platelet rich plasma versus triamcinolone versus placebo-normal saline in chronic plantar fasciitis: regenerative medicine in orthopaedics - Thimmegowda, Darshan Gaddenahalli; Gowda, Lakshmisha Narasimhe; Patil, Siddanagouda; Sharanappa Parmeshwar, Siddharath; Byrareddy, Srinath (International Journal of Research in Orthopaedics, 2024)
Background: Heel pain is a common presenting condition in orthopaedic outpatient units. There are many causes of this condition, but one of the most common is plantar fasciitis. This study was conducted to find out the efficacy of a single injection of platelet-rich plasma versus steroids versus normal saline as a placebo in treating patients suffering from plantar fasciitis. Methods: Randomized single-blinded placebo-controlled trial with 3 months and 6 months follow-up using visual analogue scale and FAOS (Foot and Ankle Outcome Score) was carried out at a tertiary care hospital for a total of 120 patients (40 patients in each group). First group injected with platelet rich plasma, second group with triamcinolone and third group with normal saline. Results: Pain relief achieved in the platelet-rich plasma group and triamcinolone group was found to be statistically significant as compared to normal saline at both 3 months and 6 months follow-up. Steroid injection was associated with complications like depigmentation at the injection site and sub dermal atrophy. No complications were found with PRP or normal saline. Conclusions: This study concludes that the efficacy of a single injection of platelet-rich plasma to relieve the pain of Plantar fasciitis is better than triamcinolone or placebo over a short-term follow-up period. However, more studies are required to evaluate the efficacy of PRP over the long term with multicentric study and comparison with the currently available treatment options.